Peran Efikasi Diri dan Dukungan Sosial Teman Sebaya Terhadap Penyesuaian Diri Mahasiswa Tahun Pertama Program Studi Pendidikan Dokter Fakultas Kedokteran Universitas Udayana - Ida Ayu Gede Hutri Dhara Sasmita; I Made Rustika (Jurnal Psikologi Udayana, 2015)
Adjustment is an important mental aspects that determine a person's success in dealing with various problems in his life. The mental aspect is related to one's belief in the ability to control various obstacles and use your own potential. In addition, the mental aspect is also strongly associated with a positive response from the environment.The purpose of this research is to find out the role of self efficacy and peers social support toward personal adjustment in Medical School Udayana University. Subjects in this research were 137 first-year students Medical School Udayana University. The instruments in this research were self-efficacy scale, peers social support scale and personal adjustment scale. The result of multiple regression analysis shows R=0,605 (F=38,776; p<0,05) thus it can be stated that both self-efficacy and peers social support together contributes to personal adjustment. Determination coefficient = 0,367, which means the effective contribution of self-efficacy and peers social support to personal adjustment is 36,7%. Standardized beta coefficient of self-efficacy is 0,457 (t=5,935; p<0,05) thus it can be stated self-efficacy contribute to personal adjustment. Standardized beta coefficient of peers social support is 0,242 (t=3,141; p<0,05) thus it can be stated peers social support contribute to personal adjustment. Keywords: self-efficacy, peers social support, personal adjustment, first-year student.